Mastering Entity Framework : effortlessly produce data-driven applications for .NET to address the competing demands of data storage and data modeling with Entity Framework /: effortlessly produce data-driven applications for .NET to address the competing demands of data storage and data modeling with Entity Framework. (2015) - Singh, Rahul Rajat
No abstract available